B148 Effect of portable negative pressure units on expelled aerosols in the operating room environment. (11th August 2022) - Popovic, M; Beathe, JC; Gbaje, E; Sharp, M; Memtsoudis, SG
Abstract : Background and Aims: Spontaneously breathing patients undergoing procedures under regional anesthesia can expose operating room personnel to infectious agents. The use of localized negative pressure within proximity of a patient's airway is expected to reduce the amount of bioaerosols dispersed particularly for anesthesia staff who are frequently near the patient's airway. Methods: In the experiment, aerosols were produced using a polydisperse aerosol generator with nebulized saline. A portable negative pressure unit was set up at set distances of 10 and 30 cm with the aim of reducing aerosol particle counts detected by a laser-based particle counter. Results: Without the portable negative pressure unit, the median concentration of 0.5 µm aerosols detected was 3128 (1533, 22832) particles/ft 3 /min. With the portable negative pressure unit 10 cm and 30cm from the site of aerosol emittance, the median concentration compared to background concentration was -0.5 (-8, 8) particles/ft 3 /min and 398 (89, 1749) particles/ft 3 /min, respectively. For particle concentrations of 0.5 µm, 0.7 µm, and 1.0 µm a significant amount of aerosol reduction was observed (p<0.001). Conclusions: PNP units have the potential to mitigate risks for all operating room staff as spontaneously ventilating patients with infectious diseases of the airway can contaminate the environment. As expected the effectiveness of the aerosol particle reduction is dependent on the distance between the PNP unit and the aerosol generating site. Further experiments are warranted to assess the safety of staff when encountering a potentially infectious patient in the operating room.